Effect of Maqāsid al-Sharīʻah on Preservation of Wealth (Al-Qamar, 2022)
Money is an unavoidable part of life. Furthermore, sound money is a keeper of life. Islam's legislation supports in response to the value placed on sound money. Islam encourages people to acquire wealth through legal means, and it instructs us on how to manage it properly and how to increase it. Money, without a doubt, is one of the world's most valuable ornaments. Money is desired and adored, and Islam does not prohibit anybody from striving for and obtaining wealth as long as they do it in a good and lawful manner. This paper attempts to throw light on preservation of wealth in the preview of Maqasid Shariah.
Keywords: Maqasid Shariah; Objectives of Islamic Law; Preservation of Wealth; Money; Islam